THE USE OF PEDAGOGICAL TECHNOLOGIES IN TEACHING STUDENTS THE SCIENCE OF PHYSICAL CULTURE IN HIGHER EDUCATION - Axmedov Umidjon Usmonovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article analyzes the use of pedagogical technologies in teaching students the science of Physical Culture in Higher Education.